The Role of Psychological Flexibility in the Relationship Between Information Overload and Gen Z Career Preferences - Alamsyah, Andi Indra Saputra; Rahayu, Chalista Suci; Aprilia, Dela Setyo; Aisyah, A. Indira Nurul (Prodi Pendidikan Ekonomi Universitas Balikpapan, 2026)
This study examines the relationships between information overload, psychological flexibility, and career preference among Generation Z in the digital era. Grounded in cognitive and behavioral decision-making theories, the research investigates psychological flexibility as a key mechanism linking digital information exposure to career preference formation. A quantitative approach was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software. Data were collected from 100 Gen Z respondents through a structured questionnaire measured on a Likert scale. The measurement and structural models were evaluated using validity, reliability, and bootstrapping procedures to test the hypotheses. The results show that information overload has a significant positive effect on psychological flexibility, suggesting that Gen Z may develop adaptive cognitive and coping mechanisms in response to high levels of digital information exposure. Psychological flexibility also significantly influences career preference, highlighting its role in facilitating adaptive and value-based career decision-making. However, information overload does not have a significant direct effect on career preference, indicating that its influence is indirect rather than direct. Furthermore, psychological flexibility significantly mediates the relationship between information overload and career preference. Overall, the findings indicate that career decision-making among Gen Z is primarily psychologically mediated in digital environments